Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Swelling behavior and diffusion studies of high-water-retaining acrylamide/potassium methacrylate hydrogels - Mohan, Y. M.; Murthy, P. S. K.; Rao, K. M.; Sreeramulu, J.; Raju, K. M. (Journal of Applied Polymer Science, 2005)
Poly(acrylamide-co-potassium methacrylate) hydrogels were prepared by free-radical simultaneous polymerization with aqueous solutions of acrylamide (AAm) and potassium methacrylate (KMA) with a redox initiator. The copolymerization was performed with eight different compositions of KMA at a fixed concentration of oil-soluble crosslinkers, including 1,4-butanediol diacrylate and ethylene glycol dimethacrylate (EGDMA). For every composition of AAm/KMA copolymer, the percentage swelling, swelling equilibrium, and diffusion characteristics were investigated. The copolymers were further studied for deswelling properties. The power law relationships of the hydrogels were evaluated for variation in terms of saline concentration. The AAm/KMA copolymers were confirmed by IR spectroscopy. Thermal studies of hydrogels were performed with differential scanning calorimetry and thermogravimetric analysis. EGDMA was found to be a better crosslinker for obtaining higher swelling and deswelling properties for the AAm/KMA hydrogels. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; hydrogels; swelling

Enhancement of gas permeation properties of polybenzimidazoles by systematic structure architecture - Kumbharkar, Santosh C.; Karadkar, Prasad B.; Kharul, Ulhas K. (Journal of Membrane Science, 2006)
Systematic structural variations in thermally stable polybenzimidazole (PBI) are explored that led to a substantial improvement in gas permeation properties. Physical property determinations revealed that incorporation of hexafluoroisopropylidene and tert-butyl groups led to amorphous polymers with slightly lowered thermal stability and decreased chain packing. PBI based on 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) and 5-tert-butyl isophthalic acid exhibited 10-40 times higher permeability, while changes in selectivities for industrially important pairs ranged from modest decrease of 75% or less than that of PBI based on isophthalic acid. The O-2/N-2 selectivity was almost doubled in case of PBI based on 5-tert-butyl isophthalic acid. Gas diffusion coefficients were estimated from solubility and permeability coefficient determinations. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior. The permeability predictions for heavier gases in isophthalic acid based PBI correlated well with physical properties. The occurrence of permeation characteristics (especially P-H2 and P-H2/P-N2) near Robeson's upper bound, high thermal stability and good solvent solubility achieved by these structural modifications depicted the potential of this family of polymers as gas separation membrane materials. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; Polybenzimidazole; Sorption; thermal stability

Effect of substituent polarity, bulk, and substitution site toward enhancing gas permeation in dibromohexafluorobisphenol-A based polyarylates - Ishole, Yogesh S.; Karadkar, Prasad R.; Kharul, Ulhas K. (Journal of Polymer Science Part B-Polymer Physics, 2007)
The gas permeation properties of polyarylates were tuned by varying nature and site of substituents present on both of its monomers, viz., bisphenol and dicarboxylic acid. The phenyl rings of hexafluorobisphenol-A were substituted in asymmetric manner by polar bromine to obtain dibromohexafluorobisphenol-A. This bisphenol was polymerized with equimolar mixture of iso- and terephthalic acid (base case), bromo- and nitroterephthalic acid (polar group substituted acids), 4,4'-hexafluoroisopropylidene bis(benzoic acid), and t-butyl isophthalic acid (bulky group containing acids). Physical properties and gas permeation properties of these polyarylates were investigated to assess combined effects of asymmetric nature of bisphenol substitution, polar nature of substituent bromine, hexafluoroisopropylidene group present at the bridge position of bisphenol, and substituent present on the acid moiety. The combination of these substituent types led these polyarylates to lie near Robeson upper bound. The gas sorption analysis and estimation of diffusivity in these polyarylates shed a light on observed variations in gas permeation properties by attempted structural variations. (c) 2007 Wiley Periodicals, Inc.
Keywords: asymmetric substitution; Diffusion; Gas permeation; gas sorption; polyarylates; selectivity; structure-property relations

Gas sorption and transport in polyarylates: effect of substituent symmetry and polarity - Karadkar, Prasad B.; Kharul, Ulhas K.; Bhole, Yogesh S.; Badhe, Yogesh P.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Journal of Membrane Science, 2007)
The gas sorption properties of polyarylates based on bisphenol-A possessing symmetric/asymmetric substitution by nonpolar -CH3 group and symmetrically linked terephthalic acid were examined. The effects of substitution of polar bromine on terephalic acid moiety of polyarylate based on asymmetrically substituted bisphenol were also studied for physical, sorption and transport properties. The estimation of dual mode sorption parameters, solubility and diffusion coefficient revealed that nature of the substituent and substitution type plays a crucial role in depicting permeation properties. An asymmetric substitution by -CH3 group increased solubility coefficient of pure gases (N-2, O-2, CH4 and CO2) up to 27% and symmetric substitution increased the same up to 106%. This was coupled with 7-35% increase in solubility selectivity in both cases of substitution, which ascertained the usefulness of methyl group substitution in polyarylates based on terephalic acid. The pressure dependency of solubility coefficients and solubility selectivity was also investigated for these polyarylates. The sorption and transport properties of these polyarylates correlated well with physical properties of polyarylates and gases studied. The sorption/desorption kinetics of symmetrically substituted TMBisA-T was performed in order to deduce time dependent sorption behavior and to evaluate diffusivity coefficient. The apparent diffusion coefficients from sorption kinetics, desorption kinetics and from steady-states permeation-sorption were compared. The diffusion coefficients of CH4 and N-2 deduced by these methods correlated well with each other. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diffusion; kinetics; permeation; polyarylates; Sorption

Self-diffusion coefficient of ring polymers in semidilute solution - Iyer, Balaj V. S.; Shanbhag, Sachin; Juvekar, Vinay A.; Lele, Ashish K. (Journal of Polymer Science Part B-Polymer Physics, 2008)
In a topologically constraining environment the size of a flexible nonconcatenated ring polymer (macrocycles) and its dynamics are known to differ from that of linear polymers. Hence, the diffusion coefficient of ring polymers can be expected to be different from linear chains. We present here scaling arguments for the concentration and molecular weight dependence of self-diffusion coefficient of ring polymers in semidilute solutions, and show that contrary to expectations these scaling relations are identical to what is known for linear polymers. At higher concentrations excluded volume interactions arising from possibilities of segmental overlap can become effective for large ring polymers. In this regime the diffusion coefficient of large ring polymers shows a relatively weaker dependence on concentration and molecular weight. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2370-2379, 2008
Keywords: Diffusion; Macrocycles; Monte Carlo simulation

Polymer crystallization in the presence of ``sticky'' additives - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2009)
The effect of ``sticky'' additives (viz., those that have attractive interactions with the polymer) on polymer crystallization, has been investigated by dynamic Monte Carlo (DMC) simulations. Additive-polymer attractive interactions result in a slowing down of the polymer chain diffusivity in the melt state. Our results show that with increasing additive stickiness, polymer crystallinity decreases monotonically, and thinner crystallites form, viz., crystallization is inhibited by the presence of sticky additives. Unusually, the observed ``specific heat'' peak at the phase transition shows nonmonotonic behavior with additive stickiness, and exhibits a maximum for intermediate values of additive stickiness. While the origins of this unexpected behavior are not clear, we show that it correlates with a large interchange between crystalline and amorphous states of the monomers, in the vicinity of the additives. At this intermediate additive stickiness, we also find that crystallization follows a qualitatively different route-crystallinity shows a non-Avrami-like evolution, unlike the case at low or high additive stickiness.
Keywords: Additives; amorphous state; crystallisation; crystallites; Diffusion; Monte Carlo methods; polymer melts

Investigation of gas permeation properties of systematically modified polybenzimidazoles by N-substitution - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Gas permeation behavior of a series of thermally stable N-substituted polybenzimidazoles by systematically varying bulk and flexibility of the substituent was investigated. Two different PBIs having variation in their acid moiety, viz., PBI-I (based on isophthalic acid) and PBI-BuI (based on 5-tert-butyl isophthalic acid) were selected for N-substitution by alkyl groups possessing different bulk and flexibility. These substituent groups were methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. Pure gas sorption and permeability using H(2), N(2), O(2), CH(4) and CO(2) were investigated and correlated with physical properties of formed polymers. Estimation of dual-mode sorption parameters, coefficients of sorption, permeability and diffusion for different gases provided an insight towards effects of nature of a substituent group and parent PBI on governing gas sorption and permeation properties. By changing the substituent group, diffusivity coefficients was found to vary to a larger extent than the solubility coefficient. This significantly enhanced gas permeability for different gases by 1.2-129 times than that of parent PBIs. The permselectivity P(O2)/P(N2) was increased (up to 237%), while for other gas pairs, it was decreased to a different extent. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; N-Substitution; Polybenzimidazole; Sorption

New N-substituted ABPBI: synthesis and evaluation of gas permeation properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Aromatic poly(2,5-benzimidazole), ABPBI was post-modified for the first time to produce organosoluble N-substituted ABPBI. This modification was carried out by N-substitution of ABPBI with bulky alkyl groups, viz., 4-tert-butylbenzyl and methylene trimethylsilyl in an attempt to utilize high rigidity of ABPBI towards gas permeation. These substituted polymers exhibited solubility in common organic solvents, enhancing their processability than ABPBI, which is soluble only in acidic solvents. Considerable decrease in chain packing density led to increase in gas sorption as that of unsubstituted ABPBI. The permeability of pure gases of commercial significance (He, H(2), N(2), O(2), CH(4) and CO(2)) were high, coupled with attractive selectivities. In comparison to conventional PBI, methylene trimethylsilyl substituted ABPBI led to considerably high (33 folds) CO(2) permeability with almost similar selectivity (P(CO2)/P(N2) approximate to 33). Feasibility of these N-substituted ABPBIs to be converted in to required membrane form along with its considerably higher permeation properties depicted the potential of this polymer to be used as gas separation material. Gas diffusion coefficients were estimated from solubility and permeability coefficient. These, along with dual-mode sorption parameters estimated from sorption isotherms provided an insight towards variations in permeation behavior caused by the substitution. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 5-benzimidazole); Diffusion; Gas permeation; N-Substitution; Poly(2; Sorption

Shear induced diffusion in dense granular flows - Orpe, Ashish V.; Rycroft, Chris H.; Kudrolli, Arshad A. (IUTAM-ISIMM Symposium on Mathematical Modeling and Physical Instances of Granular Flows, 2010)
The dynamics of dense granular flows subjected to gravity induced shear are investigated experimentally using the refractive index matching technique. The system consists of grains flowing inside a bin with a rectangular cross-section and sheared by a rough boundary on one side and smooth boundaries on the remaining sides. The particles flow within a viscous interstitial liquid having the same refractive index as particles and are imaged in the bulk using laser fluorescence. The particle positions are identified very accurately and tracked over long durations to obtain the mean and fluctuating properties. The shear is observed to be non-linear and localized in a region of 3 to 4 particles near the boundary. The boundary imposes a packing order, and the grains are observed to flow in layers, parallel to the shearing boundary, which get progressively more disordered with distance from the walls. We have also carried out soft particle simulations in a equivalent system incorporating the Cundall-Strack contact model between the particles and ignoring the hydrodynamic effects of the interstitial liquid to understand the effect of particle friction coefficient, elasticity, contact model and polydispersity on the mean and fluctuating flow properties. We find the mean velocity and the number density of the particles as a function of flow cross-section and the particle fluctuation properties observed in the experiments and the simulations to in very good agreement after appropriate scaling.
IUTAM-ISIMM Symposium on Mathematical Modeling and Physical Instances of Granular Flows, Reggio Calabria, ITALY, SEP 14-18, 2009
Keywords: DEM; Diffusion; granular; index matching; LAMMPS; laser fluorescence

Effect of the surface roughness of conducting polypyrrole thin-film electrodes on the electrocatalytic reduction of nitrobenzene - Adhikari, Arindam; Radhakrishnan, S.; Vijayan, M. (Journal of Applied Polymer Science, 2012)
Conducting polypyrrole (PPy) thin-film electrodes were prepared by the electropolymerization of pyrrole on gold-coated glass plates. Films of various roughnesses were obtained by the variation of the scan rates during electropolymerization. These thin films were modified by doping with 6mM of the dopant NiCl2. The surface morphology of the films was studied by scanning electron microscopy and atomic force microscopy (AFM), which suggested films prepared with a high scan rate were rougher in nature than the films produced with a low scan rate. The electrocatalytic reduction of nitrobenzene was carried out with these electrodes with the cyclic voltammetry technique in acetonitrile containing 0.1M HClO4 as a supporting electrolyte. The various results obtained show that the conducting PPy thin-film electrodes were catalytically active toward the electroreduction process. The modified PPy film electrodes doped with NiCl2 were more active toward nitrobenzene electroreduction than the PPy film alone. The results indicate that the roughness of the films played a very important role in determining their catalytic activity. The PPy films that were more rough in nature were catalytically more active than the smooth films; this may have been due to the availability of more reactive sites in the case of rough films. The apparent diffusion coefficients of the PPy film electrodes were also calculated. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: atomic force microscopy (AFM); conducting polymers; Diffusion; surface modification; Thin films

pH Sensitive graft copolymers for zero order drug release: a mechanistic analysis - Muthusamy, Ramesh; Kulkarni, Mohan Gopalkrishna (Drug Development and Industrial Pharmacy, 2012)
Aliphatic polyesters containing pendent unsaturation were synthesized by the polycondensation of a diol, dicarboxylic acid and glycidyl methacrylate. Grafting methacrylic acid (MAA) resulted in graft copolymers containing polyester backbone and MAA grafts. Depending on composition, the polymers swelled extensively and eroded or dissolved at near neutral pH but remained in collapsed state at acidic pH. Three representative drugs differing in solubility, viz., Diltiazem hydrochloride (DH), Indomethacin (IM) and Verapamil hydrochloride (VH) were released at constant rate from tablets made by compressing spray-dried microparticles. The release of DH at constant rate has been attributed to increase in diffusion coefficient of the drug from the swollen layer of matrix. The release of IM and VH at constant rate was governed by erosion and was enhanced in matrices which undergo dissolution. The release rate was enhanced with increasing MAA content and the frequency of grafts along the polyester backbone. Once a day dosage forms for drugs differing in solubility have been developed using a single polymer matrix which is easy to manufacture.
Keywords: Diffusion; erosion; Graft copolymer; matrix tablets; microparticles; spray drying; sustained release

Biodegradation of phenol by the yeast candida tropicalis: an investigation by NMR spectroscopy - Phalgune, U. D.; Rajamohanan, P. R.; Gaikwad, B. G.; Varma, R. J.; George, S. (Applied Biochemistry and Biotechnology, 2013)
The process of phenol biodegradation by the yeast Candida tropicalis NCIM 3556 in aqueous medium was studied by H-1, C-13, and DOSY NMR techniques. Samples at regular intervals were centrifuged to separate the cells, and H-1 spectral data were collected at 400 MHz. Though a gradual decrease in the concentration of phenol was observed, after an incubation period of similar to 8 h, formation of any intermediate products could not be detected. Experiments carried out with uniformly C-13-labeled phenol also failed to detect formation of any carboxylic acid intermediates during degradation. The studies indicated that the phenol was completely degraded to carbon dioxide and water in approximately 20 h. Self-diffusion coefficient measurements showed that the lifetime of phenol in the bound form is too small to impart any change in its diffusion behavior and the intermediates formed are converted to carbon dioxide and water at a very fast rate.
Keywords: biocatalysis; Carboxylic acid; Diffusion; Enzyme; NMR spectroscopy; phenol